Analytical investigation of the measures to be taken against weak storey irregularities - Cansiz, Sinan (Revista de la Construcción. Journal of Construction, 2023)
Due to the earthquakes that have occurred in recent years, heavy damage has occurred in many structures in the world. When the damages occurred after the earthquakes have been examined, it has been observed that the damage occurred frequently in certain structures. These structures are generally structures with different shear capacity due to different story heights. This type of damage is defined as weak-soft storey irregularity in earthquake codes. For this reason, the use of reinforced concrete walls is recommended in the earthquake codes that have been updated in recent years. In addition, it is recommended by many researchers to strengthen the structures with various cross-frames on the storey where weak storey occur in such structures. For this purpose, a pushover analysis of structures with various storey heights and storey numbers supported by various cross-frames has been carried out. For this purpose, seismic analysis of 60 reinforced concrete structures has been made with the Seismo-Build program. In this study, the effectiveness of cross frames used in buildings with reinforced concrete wall and weak storey irregularities has been investigated.